The Differences In Quality of Sleep Among Babies Aged 3-12 Months Before and After A Baby Massage’s Class - Swandari, Riska; Suminar, Ervi (Fundamental and Management Nursing Journal, 2024)
Introduction: The toddler years are a golden period for growth and development. One effort that parents can make to help improve the quality of their baby's sleep is by doing massage. Babies who get a massage will be able to sleep soundly, so that when they wake up their concentration is full. This study aims to prove whether there is a difference in quality of sleep among babies aged 3-12 months before and after a baby massage’s at Muhammadiyah Gresik Hospital, Indonesia Methods: This research used a Pre-Experimental Design One Group Pre-Post Test Design using a sample of 34 subjects selected using a purposive sampling technique. The data instrument is in the form of an observation sheet before and after the massage. The variable measured in this study was improving the quality of the baby's sleep. Wilcoxon sign rank test analysis obtained a p value = 0.000. Results: In babies aged 3-12 months before the baby massage was carried out, the results showed that the majority of babies experienced good quality sleep, 18 (53%) babies, and after the massage, the majority of babies experienced good quality sleep, 25 (74%) babies. Conclusions: There are differences in quality of sleep among babies aged 3-12 months before and after baby massage in the baby massage class at Muhammadiyah Gresik Hospital, Indonesia. The importance of the influence of sleep on infant development because sleep is a physiological process that alternates with longer periods of wakefulness. Sleep has enormous benefits for their growth and development and optimizes their brain development, because sleep activity is one of the stimuli for the process of brain growth and development. Further research involves a larger number of samples is highly suggested.